BAHAN BELAJAR MENDENGARKAN BAHASA INDONESIA UNTUK PENUTUR ASING DI TIONGKOK - Yanto, The Hery (Hiski Malang, 2024)
This case study looks at the design and implementation of using stories to learn listening skills in Indonesian Language Department, Zhejiang Yuexiu University of Foreign Languages. The goal is to show that stories can help students acquire listening skills and learn the social-cultural values of society. This research draws upon mostly the instructor self-evaluation and students’ evaluation of the course to identify the successes and shortcomings of the learning. Materials use to present and analyze the learning process include portfolio of instructional activities, lesson plans, lesson evaluations, and students’ evaluation questionnaire. This study followed the learning of 26 students enrolled in the course for one semester. This case example shows how the instructional design principles effectively the instruction with clear guideline for assigning instructional strategies, selecting learning techniques, and choosing learning materials to motivate students and increase their active participation in completing tasks while learning. Although the course slightly difficult for them, the students stated that their listening skills improved, and they also learned other linguistic aspect of the language and the social-cultural values of Indonesia.